Nuclear magnetic resonance quantum computation - Jones, J (2004)
Nuclear Magnetic Resonance (NMR) is arguably both the best and the worst technology we have for the implementation of small quantum computers. Its strengths lie in the ease with which arbitrary unitary transformations can be implemented, and the great experimental simplicity arising from the low energy scale and long time scale of radio frequency transitions; its weaknesses lie in the difficulty of implementing essential non-unitary operations, most notably initialisation and measurement. This course will explore both the strengths and weaknesses of NMR as a quantum technology, and describe some topics of current interest.